2005
DOI: 10.1111/j.1532-5415.2005.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity Profile of Dementia Patients in Primary Care: Are They Sicker?

Abstract: Multiple medical comorbid conditions are common in older adults with and without dementia in primary care. Despite their cholinergic deficit, a substantial proportion of patients with dementia are exposed to anticholinergic medications. Models of care that incorporate this medical complexity are needed to improve the treatment of dementia in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
252
2
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 245 publications
(278 citation statements)
references
References 37 publications
9
252
2
15
Order By: Relevance
“…Ten studies 2,12,14,91,118,119,121,127,142,143 reported the prevalence of stroke in people with dementia and two studies 101,134 reported the prevalence of stroke in people with cognitive impairment. Prevalence rates varied from 3% in hospitalised older people in the UK 12 to 34% in a sample of urban and rural community-dwelling people with cognitive impairment in the USA (Figure 4).…”
Section: Strokementioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies 2,12,14,91,118,119,121,127,142,143 reported the prevalence of stroke in people with dementia and two studies 101,134 reported the prevalence of stroke in people with cognitive impairment. Prevalence rates varied from 3% in hospitalised older people in the UK 12 to 34% in a sample of urban and rural community-dwelling people with cognitive impairment in the USA (Figure 4).…”
Section: Strokementioning
confidence: 99%
“…Thirteen studies reported the prevalence of diabetes in populations of people with dementia 2,12,14,91,118,119,121,127,128,142,143 or MCI. 101,134 Prevalence rates varied from 6% to 39%.…”
Section: Diabetesmentioning
confidence: 99%
See 3 more Smart Citations